Thermodynamic properties of TPI shape memory polymer composites reinforced by GO/SiO2 modified carbon fiber. (28th July 2022) - Xu, Lidan; Zhao, Jitao; Shi, Mingfang; Liu, Jingbiao; Wang, Zhenqing
Abstract: The modified carbon fiber reinforced trans -1, 4-polyisopren (TPI) shape memory polymer composites were prepared by deposition of GO/SiO2 on the surface of carbon fiber through electrostatic interaction. The interfacial bonding between TPI matrix and modified carbon fiber, thermodynamic properties and shape recovery ability of TPI shape memory polymer composites were systematically characterized and analyzed. Results show that while guaranteeing the shape memory effect of polymer composite, the introduction of modified carbon fiber significantly increased the thermodynamic properties and interface strength of TPI shape memory polymer composite. When the number of GO/SiO2 self-assembled layers on carbon fiber surface was four, the corresponding composite sample had excellent shape memory performance and the best thermodynamic performance. Graphical abstract: Shape recovery rate vs. temperature relationship of carbon fiber reinforced composite samples with different number of self-assembly layers. Image 1